A huge diamondoid metal–organic framework with a neo-mode of tenfold interpenetration1. Issue 15 (21st April 2015) - Tseng, Tien-Wen; Luo, Tzuoo-Tsair; Tsai, Chen-Chuan; Lu, Kuang-Lieh
<x xml:space="preserve">Abstract</x> A huge diamondoid framework with edge distances of the adamantane cages of up to 25.95 Å, is reported. This MOF displays a tenfold interpenetration, which is constructed from bulky and elongated aromatic-rigid dicarboxylate scaffolds, exhibits a self-catenated net with a point symbol of {(62.84)(64.8.10)2}.